Implementation of the School Literacy Movement as an Effort to Grow Interest in Reading in Grade 2 Students of SD Negeri 2 Tegal Maja for the 2023/2024 Academic Year - Pratiwi, Wintianur Kamala; Fitriana, Maulida Arum; Mardianti, Nunung (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
This research aims to describe the implementation of the school literacy movement as an effort to foster interest in reading in grade 2 students at SD Negeri 2 Tegal Maja. This research was conducted at SD Negeri 2 Tegal Maja, Tegal Hamlet, Tanjung Village, Tanjung Klu District. This research is descriptive qualitative research. Data collection techniques were carried out using interviews, observation and documentation. The results of the research show that the implementation of the School Literacy Movement (GLS) carried out by SDN 2 Tegal Maja has been running since 2019, where this program is running very well because all school members support and participate with each other in the program in order to create a literate school community throughout life. The GLS applied really helps students to understand, read, write and listen in teaching and learning activities. GLS at SDN 2 Tegal Maja is implemented through several activities, including: providing libraries, creating reading corners, educational classroom walls and reading subject books before teaching and learning activities begin. The supporting factor in implementing GLS at SDN 2 Tegal Maja is that when the highest leadership of the institution is committed to carrying out a task, it will be carried out well. The enthusiasm of teachers, students and managers of School Literacy Movement activities, the availability of reading corner facilities. The obstacle is the limited number of suitable books/reading materials.